Disadvantage among Australian Young Mothers - Bradbury, Bruce (My University, 2006)
Young mothers are one of the most disadvantaged groups in Australian society. This paper documents this disadvantage and shows how the relative disadvantage of young mothers has increased over time. Almost all teenage mothers and most mothers in their early 20s are reliant upon income support payments and both groups have low levels of education. By the time they are in their early 30s, women who were young mothers are less likely to be partnered, if partnered are more likely to have a low-income partner, and are less likely to be purchasing their own home. This concentration of disadvantage has increased over the last 20 years. The main reasons for this disadvantage lie in the factors that determine fertility at young ages rather than via the effect of young motherhood per se. Nonetheless, young motherhood is a strong signal of disadvantage, which could be used in the appropriate targeting of support services to disadvantaged mothers and their children.
Australian Journal of Labour Economics
Keywords: Families; Disadvantage; Families -- Mothers; Families and relationships; Families; Disadvantage; Mothers; Families and relationships